2021
DOI: 10.3389/fmats.2021.739859
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Carbon Boosted the Formation of Few-Layered MoS2 for High-Performance Lithium and Sodium Storage

Abstract: Molybdenum sulfide (MoS2) has become a potential anode of lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) due to its high theoretical capacity and low cost. However, the volume expansion, poor electrical conductivity and dissolution of polysulfides in the electrolyte during the cycling process severely limited its applications. Herein, few-layered MoS2@N-doped carbon (F-MoS2@NC) was synthesized through a facile solvothermal and annealing process. It was found that the addition of N-doped carbon pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the GCD plots of MoS 2 /C-1-700 at different current densities are displayed in Figure d, which further highlight its rapid Na storage reactions and low polarization potential, even at 5 A g –1 . Moreover, in comparison to many other carbonous MoS 2 anodes reported, MoS 2 /C-1-700 exhibits superior rate performances, as shown in Figure e. The EIS measurements are also used to evaluate electrical charge behavior, which can further prove the rapid Na + storage of the samples. As shown in Figure f, in comparison to MoS 2 /AC-1-700 and bulk MoS 2 , the charge transfer resistance ( R ct ) of the MoS 2 /C-1-700 composite is approximately 218.2 Ω, smaller than that of MoS 2 /AC-1-700 (338.8 Ω) and MoS 2 (222.4 Ω).…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, the GCD plots of MoS 2 /C-1-700 at different current densities are displayed in Figure d, which further highlight its rapid Na storage reactions and low polarization potential, even at 5 A g –1 . Moreover, in comparison to many other carbonous MoS 2 anodes reported, MoS 2 /C-1-700 exhibits superior rate performances, as shown in Figure e. The EIS measurements are also used to evaluate electrical charge behavior, which can further prove the rapid Na + storage of the samples. As shown in Figure f, in comparison to MoS 2 /AC-1-700 and bulk MoS 2 , the charge transfer resistance ( R ct ) of the MoS 2 /C-1-700 composite is approximately 218.2 Ω, smaller than that of MoS 2 /AC-1-700 (338.8 Ω) and MoS 2 (222.4 Ω).…”
Section: Resultsmentioning
confidence: 95%
“…That review article also covers the nitrogen enrichment techniques using different types of molecules (i.e., amines, nitrogen enrichment techniques, and nitric acid). Li et al (2021) found that the incorporation of N-doped carbon in hybrid materials formed by few-layers MoS 2 @N-doped carbon resulted in high-performance lithium and sodium storage. It was claimed that the incorporation of N-doped carbon material avoided the agglomeration of MoS 2 nanocrystals, improved the electron transport capacity, and the stress of MoS 2 during charge/discharge process.…”
Section: Chemical Surface Propertiesmentioning
confidence: 99%
“…The functionalization is necessary for the growth of flat MoS 2 . Another strategy to enhance the quality of MoS 2 structure was performed by Li et al (2021), who observed that the existence of N-doped carbon promotes the formation of few-layered MoS 2 structures in the solvothermal synthesis of MoS 2 @NC hybrid material. On the other hand, Jangir et al ( 2019) prepared a nitrogen-doped reduced graphene oxide matrix from Tassar silk cocoon containing Li and S. Then, Mo was introduced in the carbon matrix which produced the formation of MoS 2 layers on the surface of the material.…”
Section: Other 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nitrogen-doped carbon is recommended with MoS 2 to create the extrinsic conductivity which enhances the contact between carbon and MoS 2 [113,114]. A few-layered MoS 2 @N-doped carbon (F-MoS 2 @NC) as anode in SIBs maintains a reversible capacity of 171 mAh g -1 at a high current density of 1000 mA g -1 after 600 cycles due to N-rich carbon which has extrinsic conductivity and increased contact between carbon and MoS 2 [115]. In addition, different layers of MoS 2 nanosheets having a large interlayer distance of 1.0~1.1 nm (vs. 0.62 nm for pristine MoS 2 ) effectively promote the transport of ions between the electrodes and electrolyte during charging and discharging processes, thus improving the performance [114,116].…”
Section: Carbon Quantum Dotsmentioning
confidence: 99%